2008
DOI: 10.1016/j.icarus.2007.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Main belt binary asteroidal systems with eccentric mutual orbits

Abstract: ABSTRACTanother S-type asteroid, and should be poorly fractured as well. (379) Huenna seems to display both characteristics: the moonlet orbits far away from the primary in term of stability (20% × R Hill ), but the primary's porosity is significant (30-60%).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
68
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 44 publications
(82 reference statements)
6
68
1
Order By: Relevance
“…Its first satellite was discovered in 2002 using an AO system mounted on the Gemini North telescope. Marchis et al (2008a) attempted to derive the orbital parameters of this 2-km satellite diameter and found a solution with the satellite describing a highly eccentric orbit (e ∼ 0.9 and a ∼ 290 km) around the primary in 60−70 days. More recently, a careful photometric analysis of the lightcurves of Balam suggested that the primary of the system is in fact composed of two components with 6 and 2 km diameters orbiting at 20 km (Marchis et al 2008b).…”
Section: Orbital Solutions For (3749) Balam Outermost Companionmentioning
confidence: 99%
See 4 more Smart Citations
“…Its first satellite was discovered in 2002 using an AO system mounted on the Gemini North telescope. Marchis et al (2008a) attempted to derive the orbital parameters of this 2-km satellite diameter and found a solution with the satellite describing a highly eccentric orbit (e ∼ 0.9 and a ∼ 290 km) around the primary in 60−70 days. More recently, a careful photometric analysis of the lightcurves of Balam suggested that the primary of the system is in fact composed of two components with 6 and 2 km diameters orbiting at 20 km (Marchis et al 2008b).…”
Section: Orbital Solutions For (3749) Balam Outermost Companionmentioning
confidence: 99%
“…More recently, a careful photometric analysis of the lightcurves of Balam suggested that the primary of the system is in fact composed of two components with 6 and 2 km diameters orbiting at 20 km (Marchis et al 2008b). We know that Marchis et al (2008a) solution is flawed since they attempted to fit the position of the satellite when it was closer to its primary, confusing the outer and the inner moon position (the inner moon was unknown at the time of this analysis). Additionally, recently published observations of the triple system in the mid-infrared with Spitzer/IRS by Enriquez et al (2010) were used to derive the equivalent size D eq = 4.68 ± 0.54 km, leading to an unrealistic average density of 8 g/cm 3 based on the orbital solution of Marchis et al (2008a).…”
Section: Orbital Solutions For (3749) Balam Outermost Companionmentioning
confidence: 99%
See 3 more Smart Citations